2015
DOI: 10.1016/j.jacc.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Catastrophic Adverse Outcomes in Children With Pulmonary Hypertension Undergoing Cardiac Catheterization

Abstract: Background Cardiac catheterization is the standard of care procedure for diagnosis, choice of therapy, and longitudinal follow-up of children and adults with pulmonary hypertension (PH). However, the procedure is invasive and has risks associated with both the procedure and recovery period. Objectives Identify risk factors for catastrophic adverse outcome in children with PH undergoing cardiac catheterization. Methods We studied children and young adults 0-21 years of age with PH undergoing ≥1 cardiac cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 31 publications
2
50
0
5
Order By: Relevance
“…NTproBNP is a cardiac biomarker of chamber distention and therefore is used as a general diagnostic standard for heart failure with poor discrimination of right or left ventricular etiology (8,9). Cardiac catheterization, the invasive method, can be complicated by accruing morbidity and mortality risk, particularly in pediatric patients (10)(11)(12).…”
mentioning
confidence: 99%
“…NTproBNP is a cardiac biomarker of chamber distention and therefore is used as a general diagnostic standard for heart failure with poor discrimination of right or left ventricular etiology (8,9). Cardiac catheterization, the invasive method, can be complicated by accruing morbidity and mortality risk, particularly in pediatric patients (10)(11)(12).…”
mentioning
confidence: 99%
“…al 2007 realizado por medio de una cohorte retrospectiva en pacientes con y sin presencia de anomalía congénita sometidos a cateterismos cardíaco identifi có que los pacientes con hipertensión pulmonar en rangos sistémicos o supra-sistémicos se asociaron con mayor frecuencia a la presencia de complicaciones mayores (paro cardiaco, arritmias y muerte)(7); lo cual contrasta con los hallazgos aquí reportados donde ningún paciente falleció durante el procedimiento. De otro lado, la asociación de algún tipo de anomalía congénita con hipertensión pulmonar ha sido relacionado a un mayor riesgo anestésico durante el cateterismo cardíaco (2). Todos los anteriores factores de riesgo (HTP severa, anomalía congénita, alteraciones en los parámetros hemodinámicos) proveen un efecto que al fi nal puede ser aditivo, considerando un alto riesgo general de eventos críticos durante la anestesia en la población de estudio (8).…”
Section: Discussionunclassified
“…La principal complicación que se presentó en el estudio fue la crisis de hipertensión pulmonar (9%), no obstante, no se presentaron muertes intraoperatorias; resultados que están acordes a la evidencia de otros estudios no restringidos a pacientes con anomalías congénitas donde la mortalidad oscila entre 0.3 y 0.8% (2). E contraste, la mortalidad en la población analizada fue considerablemente mayor en el período postquirúrgico alcanzando un valor de 11% durante los 30 días posteriores al cateterismo; este valor tal elevado podría tener relación con alta complejidad que en general representan las patologías congénitas, el compromiso del estado basal de paciente, las múltiples comorbilidades y su condición sociocultural que podría impactar negativamente en la detección y atención temprana en este grupo de pacientes.…”
Section: Discussionunclassified
“…Both single‐center and pooled registry data have shown that children with PH undergoing HC have a high risk of major AEs (3.5%–6.2%) and death (0.2%–1.4%) 4, 6, 7, 8, 9, 10, 11, 12, 13, 14. However, there are limited data identifying important risk factors for major AE and death in the pediatric PH population.…”
mentioning
confidence: 99%
“…Risk factors (OR)11: prematurity (4.95), infants without prematurity (1.61), cardiac surgery during the same admission, prior heart transplantation (2.78), hemodialysis (19.40)…”
mentioning
confidence: 99%